Estudio de la expresión oral y corporal en el desenvolvimiento de los estudiantes de la Carrera de Comunicación Social de la UTB Ext. Quevedo, año 2021 - Zamora Solis, Valeria Yamileth (2021)
Oral and body language are fundamental elements in social communication, the two complement each other, since language is an instrument to communicate and communication needs body language to complement each other. When speaking of oral and corporal communication we also speak of the particular way of expressing people. That is why a communicator must express himself correctly so that it is understood by his audience, acquiring credibility and professionalism. This investigative work was carried out with students of the social communication career of the Technical University of Babahoyo ext. Quevedo with the objective of analyzing oral and corporal expression in the development as students and future communication professionals. The methodology used was documentary and descriptive, the survey was used as a means of collecting information. The main findings show that the learning of oral and corporal expression is very important for the professional development of social communication, however, it presents a problem since the necessary knowledge does not exist for its It is concluded that written work, training and workshops given by teachers in order to provide knowledge and development in the communication field.